2018
DOI: 10.1007/s11547-017-0843-6
|View full text |Cite
|
Sign up to set email alerts
|

Uterine fibroid embolization efficacy and safety: 15 years experience in an elevated turnout rate center

Abstract: UFE represents an excellent alternative to surgical treatment: it is safe, tolerable and effective both in short and long term, with evident advantages in economic and social terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 72 publications
0
9
0
4
Order By: Relevance
“…Regarding gynecological and obstetric diseases, interventional radiologists are very familiar with the pelvic vascular anatomy based on previous experience with embolization for pelvic trauma in addition to the growing experience with uterine fibroid embolization. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Most of the interventional procedures are performed percutaneously with little associated patient discomfort and with conscious sedation instead of general anesthesia. 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding gynecological and obstetric diseases, interventional radiologists are very familiar with the pelvic vascular anatomy based on previous experience with embolization for pelvic trauma in addition to the growing experience with uterine fibroid embolization. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 Most of the interventional procedures are performed percutaneously with little associated patient discomfort and with conscious sedation instead of general anesthesia. 17 …”
Section: Introductionmentioning
confidence: 99%
“…3 ). 3 , 8 , 12 , 16 , 18 In patients affected by gynecological malignancies, endovascular treatment of metrorrhagia could be a valid therapeutic alternative, especially in elderly patients with poor clinical conditions not suitable for surgery. A bilateral and superselective embolization using nonresorbable embolic agents should be performed, except for those cases in which there is infiltration of major vessels causing pseudoaneurysms or fistulas that require embolization.…”
Section: Introductionmentioning
confidence: 99%
“…Embolization is a minimally invasive treatment, frequently using particles, to block blood flow in the targeted arteries to prevent gastrointestinal bleeding 1,2 or to starve tumors of oxygen and nutrients. 3,4 Chemoembolization involves combining chemotherapeutics with particle embolics to target high doses of anticancer drugs to tumors and, thereby, substantially reduce systemic side effects. 5 Conventional embolization therapy is usually performed under X-ray guidance, i.e., X-ray fluoroscopy or computed tomography (CT), to guide delivery of the embolic agents to the target regions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous single-center studies investigated the effectiveness of UAE and found the procedure to be successful at reducing or eliminating symptoms while also producing minimal complications [6][7][8][9]. However, these studies did not compare outcomes to alternative treatment methods.…”
Section: Introductionmentioning
confidence: 99%